The Implementation of AI-Assisted Digital Artwork Learning as an Innovative Strategy for Elementary School Teachers in Improving Student’s Technological Literacy in the Era of the Independent Curriculum - Fauziah Wulansari; Riska Hartanti; Bambang Sumardjoko; Sabar Narimo (FKIP - Universitas Riau, 2026)
The advancement of digital technology and artificial intelligence (AI) presents significant opportunities for art education in elementary schools, particularly within the Independent Curriculum framework that prioritizes creativity, autonomy, and technological literacy. This study examines the implementation of AI-assisted digital art learning by elementary school teachers and its impact on students' technological literacy development. Employing a descriptive qualitative approach with collective case study design, data were gathered through observations, interviews, and document analysis in multiple elementary schools implementing the Independent Curriculum. The interactive model of Miles, Huberman, and Saldaña guided the data analysis process. Findings revealed high student enthusiasm and active engagement in prompt-based digital art activities, demonstrating increased interest in continued participation. AI integration enhanced students' creativity, conceptual comprehension, and technical proficiency in digital artwork creation. Furthermore, the learning process strengthened technological literacy through prompt development skills, critical evaluation of AI-generated outputs, and independent application utilization. However, challenges emerged regarding teacher preparedness, disparities in students' digital competencies, and insufficient devices and infrastructure. This study concludes that AI-assisted digital art learning represents a relevant and innovative pedagogical strategy effectively supporting Independent Curriculum implementation in elementary education.